Detection of arrhythmias in patients with cardiac amyloidosis using implantable ECG recorders. (3rd October 2022) - Taborsky, M; Aiglova, R; Fedorco, M; Bradac, P; Flasik, J; Danek, J; Schee, A
Abstract: Introduction: Cardiac Amyloidosis frequently results in congestive cardiac failure and arrhythmias, from a disruption in cardiac substrate with subsequent electro-mechanical remodeling. Arrhythmias are vary based on the amyloidosis type. Conduction defects and atrial arrhythmias are more prevalent in transthyretin amyloidosis compared with light chain amyloidosis, and this difference might be a reflection of the longer survival time in the former. Methods: 112 transthyretin amyloidosis (TTR) patients with completed underlying diagnosis including 99mTc-DPD scan, genetic testing and endomyocardioal biopsy (27%) without documented arrhythmias were randomized to standard clinical follow-up including arrhythmias or implantation of an ECG loop recorder (ILR). The classic FU took place in a heart failure clinic, and the group of patients with ILR was monitored by remote control with automatic daily report of the occurrence of arrhythmias by an independent organization. If an arrhythmia was detected, the patient was contacted immediately. The mean follow-up time for both groups was 17±7 months. Results: The results are summarized in Table 1. Conclusions: Currently, there is no consensus on the absolute benefit that ICDs in patients with cardiac amyloidosis. When non-sustained VT and syncope are captured and documented, ICD implantation for prevention of SCD in CA is most likely a reasonable approach. However, intensive monitoring of arrhythmias in patients with CA using ILR can lead to accurate and early detection of ventricular arrhythmias in particular and early initiation of ICD treatment as a prevention of SCD. Documentation of ventricular arrhythmias in CA patients was significantly higher by ILR (p<0.005) and was a clear predictor of patient survival (HR 2.51). Funding Acknowledgement: Type of funding sources: None.